(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
The study examined the impact of maritime trade financing and blue economy activities on Nigeria’s export diversification from 1995 to 2024. Despite Nigeria’s considerable maritime potential, export diversification had remained constrained due to weak sectoral financing, underdeveloped port infrastructure, and volatile macroeconomic conditions. The study aimed to evaluate both the short-run and long-run dynamics linking maritime trade financing, blue economy performance, and export diversification within a systems framework. Grounded in systems theory, the study conceptualized export diversification as the outcome of interconnected financial and productive subsystems in the maritime economy. Using annual time-series data, the study applied the Augmented Dickey–Fuller unit root test, Johansen cointegration, a Vector Error Correction Model (VECM), and diagnostic checks. The study found a significant long-run relationship among the variables, indicating that maritime trade financing and blue economy performance had positive and sustained effects on Nigeria’s export diversification, while inflation and exchange rate volatility exerted negative impacts. In the short run, adjustments were gradual but positive, indicating that the system corrected imbalances over time, with maritime trade financing and blue economy performance contributing modestly yet consistently to export diversification. The study concluded that sustainable maritime financing and efficient blue economy operations are essential for reducing Nigeria’s dependence on oil exports. It is recommended that the Central Bank of Nigeria and commercial banks expand targeted credit facilities to the maritime sector to foster inclusive and resilient export growth.